Promoting pro-environmental behavior through organizational identity and green organizational climate - Zafar, Hina; Ho, Jo Ann; Cheah, Jun‐Hwa; Mohamed, Rosmah (Wiley, 2023)
This study was conducted to explore the influence of green human resource practices on employees' voluntary pro-environmental behavior through the sequential mediation path of green organizational climate and organizational identity. A total of 459 employees from the textile industry in Pakistan participated in the study. The results were collected using two sources (managers and employees) at two time points. The proposed research model of the study was tested using structural equation modeling. The results validated the significant positive relationship between green organizational climate and organizational identity. We also found support for the serial mediation of green organizational climate and organizational identity in the green human resource management–voluntary pro-environmental behavior relationship. All the hypotheses were significant. Overall, this study explains why and how green human resource management practices lead to voluntary pro-environmental behavior. The implications for theory and practices that will enable organizations to encourage voluntary pro-environmental behavior among their employees are discussed.